P-284 Using the charityworks graduate scheme as part of a talent management strategy. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Andrews, Megan; Kallakivi, Elisa; Cain, Sam
Abstract : Background: High-performing organisations are more than twice as likely as low-performing organisations (69% and 31%) to have programmes for the attraction, development, management and retention of talent aligned to organisational strategy (Project Management Institute, 2013). There is evidence of correlation between talent management and organisational success in nursing (Taie, 2015) and the NHS Leadership Academy acknowledges that competition for skilled staff in a more global, mobile, multi-generational, diverse workforce means that talent management is a driver for success in healthcare (NHS Leadership Academy, 2014). Charityworks offer a one-year fixed-term graduate scheme that hospices can use to develop their non-clinical talent. Aim: To offer two Charityworks Graduate placements aimed at: Providing opportunities for new initiatives to be supported in key departments Providing a stepping stone for future careers Ensuring a pipeline of new talent. Methods: The hospice developed two job descriptions (Marketing Officer and Executive Assistant) for Charityworks who recruited, selected and recommended graduates for the roles. Charityworks provide training, conferences, mentoring, peer coaching, networking and research opportunities throughout the year. The hospice will evaluate using stakeholder interviews and Charityworks will publish a qualitative evaluation based on graduate and placement supervisor surveys; results from its five hospice-sector partners can be analysed. Findings: The hospice gained two promising team members in Marketing and Communications and Community Engagement, easing resource demands and supporting project development. The graduates gained access to a competitive sector, challenging roles and professional development opportunities. One graduate will be hired to a new role after their placement and the hospice would use Charityworks again. Conclusion: The Charityworks Graduate Scheme provides an opportunity for hospices to recruit from a targeted pool of candidates, offers graduates access to meaningful roles and development opportunities that hospices may not have the resource to provide internally, and can contribute to a robust talent management strategy.